2021
DOI: 10.1088/1361-6439/abf334
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of passive mixing via arc microchannel with sharp corner structure

Abstract: A novel microfluidic device for efficient passive mixing is reported. A series of sharp corner structures designed on side wall of an arc microchannel was utilized to induce three-dimensional vortices, which strongly stretched and folded the interface and significantly increased the interfacial contact area between different fluids. Additionally, the sharp corner structure induced high radial velocity and reduced the diffusion length because of the restricted effect of the geometrical structure. Eventually, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Visualization of the interface formed in the channel between the water stream and the ethanol revealed that mixing is a combination of diffusion and fluid agitation. With the cooperation of Xi'an Jiaotong University (China) and the University of Akron (USA), Huang et al 118 proposed a novel microfluidic device for efficient passive mixing, that is, a series of sharp corner structures designed on the side wall of an arc microchannel, as shown in Fig. 10(b).…”
Section: Design Principles Of Microreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visualization of the interface formed in the channel between the water stream and the ethanol revealed that mixing is a combination of diffusion and fluid agitation. With the cooperation of Xi'an Jiaotong University (China) and the University of Akron (USA), Huang et al 118 proposed a novel microfluidic device for efficient passive mixing, that is, a series of sharp corner structures designed on the side wall of an arc microchannel, as shown in Fig. 10(b).…”
Section: Design Principles Of Microreactorsmentioning
confidence: 99%
“…(b) Schematic diagrams of arc microchannels, including simple arc microchannels (channel 1), arc microchannels with sharp corners located on external walls (channel 2) and asymmetrically located on both side walls (channel 3). 118 Copyright 2021 IOP, Publishing Ltd. (c) Staggered herringbone mixer (SHM). 119 Copyright 2002, The American Association for the Advancement of Science.…”
Section: Design Principles Of Microreactorsmentioning
confidence: 99%
“…The fabrication technology for micro channels with optical access is available and well established in the field. Aided by CFD and dye shadowgraphs, the 2D (depth averaged) concentration distribution within micro mixers can be determined (Parsa and Hormozi, 2014;Bazaz et al, 2018;Chen et al, 2018;Mariotti et al, 2018;Mariotti et al, 2019;Huang et al, 2021). Confocal laser-induced fluorescence (LIF) allows even deeper insights into stationary flow systems, yielding 3D concentration fields of micro channels with high spatial resolution (Hoffmann et al, 2006;Tsai and Wu, 2011;Hermann et al, 2018;Frey et al, 2021).…”
Section: Optical Measurement Techniquesmentioning
confidence: 99%